UNDERSTANDING IN THE SYSTEM OF PHILOSOPHICAL KNOWLEDGE - DEMIRTSHYAN, MOVSES (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The article explores the place and role of understanding in the system of philosophical knowledge, as well as the development of ideas about understanding in the history of philosophical thought. The object of this study is a philosophical understanding of reality; the subject is an understanding of the text. It is argued that there is a significant difference between scientific and philosophical comprehension of reality. The goal of science is truth, while the goal of philosophy is understanding. In knowledge an object “tells” about itself, but in understanding, a person talks about an object. From this point of view, understanding is a form of humanized knowledge, when not only rational but also spiritual comprehension of reality occurs. In the article, special attention is given to hermeneutics, where understanding and text were considered among the main objects of humanitarian research. It is shown that the well-known hermeneutic triangle - “author - text - reader” is a universal form of understanding of texts in which reality becomes accessible to human thinking. On the example of the evolution of hermeneutic studies it is concluded, that none of the elements in this scheme can claim to be the starting point of understanding. Understanding is also considered as a process of forming the space of personal being, which has no physical boundaries, but only boundaries in the consciousness between learned and unknown texts. Understanding, therefore, implies free thought activity, which is another difference between understanding and knowledge: we cannot change knowledge at our discretion, since it is objective and necessary, but we can freely interpret texts and create meanings. This is due to the fact, that knowledge answers the question “What is this?”, while understanding answers the question “What does this mean for me?”
Keywords: understanding, knowledge, reflection, cognition, world exploration, meaning, interpretation, necessity, freedom, hermeneutics